Peran Ganda Perempuan dalam Perekonomian Keluarga melalui Perspektif Performativitas Gender Judith Butler - Sisy Viola Gendis Nasution; Azizah Azzahro; Nurul Kalima; Vieronica Varbi Sununianti; Istiqoma Istiqoma; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The dual role of women in family economics is a phenomenon shaped by the interplay of economic pressure and social construction within patriarchal society. This study aims to examine the dual role of women in family economics through Judith Butler's gender performativity perspective. The method used is a literature study with a descriptive qualitative data analysis approach, drawing on scientific sources published between 2020 and 2026. The findings indicate that women not only carry out domestic roles as housewives but are also actively involved in the public sphere to meet family economic needs. This condition gives rise to a double burden that affects physical exhaustion and psychological pressure. Within Butler's theoretical framework, the dual role is understood not as something natural, but as a product of social norms reproduced through repeated practices in everyday life. Nevertheless, women's participation in the public sphere has been shown to open spaces for increased independence and negotiation of gender relations within the family. This study underscores the importance of critical understanding of gender construction in order to achieve a fair and equal division of labor.